The process of research in psychology - McBride, Dawn M. (Los Angeles, Calif. : SAGE Publications, 2013)
"Utilizing numerous examples from published research, this introductory text provides a step-by-step explanation of how to design, conduct, and present a research study in psychology. Early chapters introduce important concepts for developing research ideas, subject sampling, ethics, and data collection to help students understand the process of research. Subsequent "nuts and bolts" chapters provide more detailed coverage of these topics and examine the various types of research relevant to the field of psychology. This two-part structure creates logical scaffolding upon which students can build their knowledge and guides them through the process of conducting research in psychology."--Publisher's description.
Includes bibliographical references and index.
Keywords: Psychology -- Research -- Methodology; Psychology, Experimental